Stem cell-derived exosomes prevent the development of thoracic aortic aneurysm/dissection by inhibiting AIM2 inflammasome and pyroptosis - Lin Lu; Feng Liu; Weiliang Wu; Yu Zhang; Bin Liu; Qingfang Han; Tonggan Lu; Huiling Zhang; Xi-yong Yu; Yangxin Li (Extracellular Vesicle)
Thoracic aortic aneurysm/dissection (TAAD) is a severe vascular condition associated with life-threatening complications, and its underlying molecular mechanisms remain largely unexplored. Previous research indicates that the aberrant activation of cytosolic DNA and its receptors plays a crucial role in vascular inflammation and dysfunction. Specifically, Absent in Melanoma 2 (AIM2), an intracellular DNA receptor, can trigger the inflammasome pathway, leading to extracellular matrix destruction. In this investigation, we delved into the mechanism underlying AIM2 activation in TAAD development and explored the potential of exosomes to impede TAAD progression by suppressing AIM2 expression. Our findings revealed that heightened AIM2 expression and activation contribute to TAAD development by fostering vascular inflammation and disrupting vascular homeostasis. Activated AIM2 induces pyroptosis through the recruitment of the deubiquitination enzyme USP21, which stabilizes AIM2 by reducing its ubiquitination and degradation. Moreover, we demonstrated that exosome-derived miR-485-5p exerts an anti-inflammatory and protective effect on the thoracic aorta by inhibiting AIM2 activation. This study introduces novel perspectives for the treatment of TAAD.